A Method for PLC Implementation of Supervisory Control of Discrete Event Systems - Vieira A.D. (2017)
© 2016 IEEE.This paper faces the problem of coordinating equipment operation in a flexible manufacturing system consisting of several subsystems including robots, assembling machines, CNC lathes, and mills. There are two main problems in such a system. The first is controlling each individual subsystem considering its own sensors, actuators, and specialized controller to perform a certain sequence of activities. Due to their expertise and/or application of formal methods, programmable logic controller (PLC) practitioners and equipment manufacturers develop efficient and safe solutions to address this problem. The second problem is coordinating the concurrent operation of these subsystems with the goal of producing what is requested as efficiently as possible and guaranteeing the integrity and safety of the system. Supervisory control theory (SCT) is particularly suited to this problem. This paper presents a method that allows a designer to systematically convert SCT's results into a PLC application program. The resulting program conforms to IEC 61131-3 and preserves the natural modularity of the system to be controlled and control specifications. An extension of this method allows a designer to reuse existing PLC hardware and application programs designed for the control of equipment by easily integrating with the code corresponding to the SCT solution. A major portion of this code may even be automatically generated, reducing development time and minimizing editing errors.